Reduced structural connectivity of the amygdala is associated with childhood trauma in adult patients with alcohol use disorder. (11th March 2022) - Soravia, Leila M.; Denier, Niklaus; Moggi, Franz; Grieder, Matthias; Federspiel, Andrea; Tschuemperlin, Raphaela M.; Batschelet, Hallie M.; Vollstädt‐Klein, Sabine; Wiest, Roland; Stein, Maria; Bracht, Tobias
Abstract: Childhood trauma (CT) is frequent in patients with alcohol use disorder (AUD) and may impact on adult drinking behaviour and treatment outcome. This study aimed to investigate the structural correlates of CT in AUD, focusing on the amygdala, which plays a crucial role in the neurobiology of trauma. We hypothesized reduced amygdala volume and reduced structural connectivity as quantified by fractional anisotropy (FA) and by number of streamlines in those AUD patients with a history of moderate to severe CT (AUD‐CT). T1‐weighted MP2RAGE and diffusion‐weighted imaging (DWI) 3‐Tesla MRI‐scans were acquired in 41 recently abstinent patients with AUD. We compared bilateral amygdala volume and structural connectivity (FA and number of streamlines) of pathways emanating from the amygdala between AUD‐CT ( n  = 20) and AUD without CT (AUD‐NT, n  = 21) using a mixed model multivariate analysis of variance (MANCOVA) controlling for age and gender. AUD‐CT displayed reduced FA and reduced number of streamlines of amygdalar tracts. There were no differences regarding amygdala volume. The severity of physical abuse, a subscale of the childhood trauma questionnaire, was negatively correlated with FA and with number of streamlines. AUD‐CT and AUD‐NT differ regarding structural connectivity of pathways projecting to and from the amygdala, but not regarding amygdala volume. Those alterations of structural connectivity in AUD‐CT may represent a distinguishable neurobiological subtype of AUD, which might be associated with the complex clinical picture and poorer outcome that patients with CT and AUD often present. Abstract : Patients with alcohol use disorder (AUD) and a history of childhood trauma (CT) differ regarding structural connectivity of pathways projecting to and from the amygdala but not regarding amygdala volume compared with patients with AUD without CT. Thus, patients with AUD and CT may represent a distinguishable neurobiological subtype of AUD, which might be associated with the complex clinical picture and poorer outcome that patients with CT and AUD often present.